Forensic Social Work Practices: The Process Diversion of Children Facing the Law in Yogyakarta - Idan Ramdani (UIN Sunan Kalijaga Yogyakarta, 2021)
This study describes the handling of cases of children in conflict with the law by considering the fulfillment of children's rights and the achievement of Restorative Justice. One of the implementations of restorative justice is through the diversion process. Diversion is the transfer of the settlement of children's cases from the criminal justice process to a process outside the criminal justice system. The involvement of the social worker profession in the diversion process is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Social workers who deal with legal issues are called forensic social workers. Forensic social workers have a very important role in the diversion process of Children in Conflict with the Law. The method used in this research is a descriptive method with a qualitative approach, with 7 informants consisting of 5 child protection social workers and 2 community advisors. Data collection techniques are in-depth interviews, observation and documentation studies. Data analysis techniques used are qualitative data analysis techniques through data reduction, data presentation and conclusion drawing. The results of this study indicate that the roles performed by social workers in the process of diversion of children in conflict with the law are the roles of planner, mediator, motivator, educator and broker. These roles have been carried out quite well, but there are roles that are less than optimally implemented, namely the role of an educator and a role as a broker. Keywords: ; Forensical Social Work, Diversion, Children Facing the Law Penelitian ini mendeskripsikan penanganan kasus anak yang berkonflik dengan hukum dengan mempertimbangkan pemenuhan hak anak dan pencapaian Restorative Justice. Salah satu implementasi restorative justice adalah melalui proses diversi. Diversi adalah pemindahan penyelesaian perkara anak dari proses peradilan pidana ke proses di luar sistem peradilan pidana. Keterlibatan profesi pekerja sosial dalam proses diversi diatur dalam Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak. Pekerja sosial yang menangani masalah hukum disebut pekerja sosial forensik. Pekerja sosial forensik memiliki peran yang sangat penting dalam proses diversi Anak Berkonflik dengan Hukum. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif, dengan jumlah informan 7 orang yang terdiri dari 5 pekerja sosial perlindungan anak dan 2 orang pendamping masyarakat. Teknik pengumpulan data adalah wawancara mendalam, observasi dan studi dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis data kualitatif melalui reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa peran yang dilakukan oleh pekerja sosial dalam proses diversi terhadap anak yang berkonflik dengan hukum adalah peran perencana, mediator, motivator, pendidik dan perantara. Peran-peran tersebut telah dilaksanakan dengan cukup baik, namun ada peran yang kurang maksimal dilaksanakan yaitu peran sebagai pendidik dan peran sebagai perantara. Kata Kunci: Pekerjaan Sosial Forensik, Diversi, Anak Berhadapan Hukum,